The Ways of Formation of Future Translators’ Readiness to Perform Professional Activities in the Conditions of War - Ernest Ivashkevych (Проблеми сучасної психології, 2022)
The purpose of our research is to characterize the ways of assessing the readiness of future translators to perform professional activities in the conditions of war; to identify the level of formation of students’ motivational, semantic, operational and value readiness to perform translation activities.